Edukasi Dini Untuk Wajib Pajak Masa Depan di SMK Negeri 1 Teluk Mengkudu - Siregar, Zulkifli; Tarigan, Nur M Ridha; Suprayitno, Edi; Sonata, Ilham; Yudha, Tri Kartika; Amrani; Azim, Fauzan (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Background: Tax is one of the sources of state revenue. So far, tax is the main source of domestic revenue. This can be seen in the State Budget (APBN). The government has made various efforts to increase the tax ratio, for example by providing tax education, tax amnesty, and even taking legal action against taxpayers who do not pay taxes. One of the reasons the tax revenue ratio is still low is because taxpayers' awareness and mindset to pay taxes is still relatively low. For this reason, the Faculty of Economics and Business, Islamic University of North Sumatra (UISU) held a Community Service (PkM) on early education of taxpayers to students of SMK Negeri 1 Teluk Mengkudu, Serdang Bedagai Regency. The purpose of this activity is to provide an understanding of the importance of tax as a source of state revenue, as well as to instill the importance of awareness of paying taxes. Method: Lectures and demonstrations delivered using Power point software. Results: Students' understanding of taxes was still low when the pretest was conducted before education and increased after the posttest after education. This is reinforced by the results of various tests where the average score of students' tax understanding tests before socialization was 3.12. Meanwhile, the average post-test score of students' tax understanding was 7.90. Conclusion: Community Service activities can improve the knowledge and understanding of students of SMK Negeri 1 Teluk Mengkudu about the importance of taxes and tax payments.